43.1k views
2 votes
Find the quadratic equation given that the roots are 3 and 9


User Raymie
by
4.0k points

1 Answer

8 votes

Answer:


\bold\purple{Quadratic \: \: eq {}^(n) = x {}^(2) - ( \alpha + \beta )x + \alpha \beta} \\

Sum of roots ,


( \alpha + \beta ) = (3 + 9) = 12

Product of roots ,


( \alpha \beta ) = (3)(9) = 27

Substituting the values in the above equation ,


\bold{x {}^(2) - ( \alpha + \beta )x + \alpha \beta} \\\\ \bold{⇢ x {}^(2) - (12)x + 27} \\\\ \bold\blue{ ⇢x {}^(2) - 12x + 27}

hope helpful~

User Jakub Adamek
by
5.7k points